Optimizing Community Learning Opportunities Through Training Programs in Non-Formal Educational Institutions - Pratama, Yolanda Lusiana; Shantini, Yanti; Kamarubian , Nike (JIV-Jurnal Ilmiah Visi, 2024)
Optimal learning opportunities are key to developing the potential and quality of human resources in society. However, the gap in equitable distribution of learning opportunities is still a challenge that must be overcome. This research aims to describe the optimization of training programs in non-formal education institutions as a solution in providing learning opportunities for the community. Using a qualitative approach and literature study, this research explores strategies and measures that can be implemented to improve the effectiveness of training programs in non-formal education institutions. The results show that optimizing learning opportunities through training programs in non-formal education institutions can be achieved by identifying community needs, increasing program flexibility, involving local communities, providing mentors and mentoring, providing certification, building partnerships with industry, utilizing technology, conducting periodic evaluations, providing financial assistance, and conducting effective promotion. The implementation of these measures can provide significant benefits to communities, such as increased skills and knowledge, economic empowerment, poverty alleviation, increased community participation, improved public health, women's empowerment, improved literacy and education, increased inclusiveness, fostering local innovation and development, and improved overall quality of life. This research contributes to a deeper understanding of the role of non-formal education institutions in providing optimal learning opportunities for communities and the strategies that can be implemented to optimize the positive impact of such training programs.